Antimicrobial Resistance Among Pseudomonas aeruginosa Isolated at a Tertiary Care Hospital, Nepal: A descriptive cross-sectional study - Adhikari, Ram Prasad; Khadka, Shusila; Rai, Shiba Kumar (Nepal Medical College Journal, 2025)
Pseudomonas aeruginosa is one of the common isolates from various clinical samples. Infections by it, are usually difficult to treat due to its emerging acquisition of drug resistance, limiting the therapeutic options. This study was done to determine the prevalence of P. aeruginosa and its antibiotic susceptibility patterns in our setup. A descriptive cross-sectional study was conducted over a year from April 2019 to March 2020 in the Microbiology Laboratory of Nepal Medical College Teaching Hospital, Kathmandu, Nepal in 121 non-repetitive clinical isolates of P. aeruginosa. Identification of the isolates and performance of antimicrobial susceptibility testing were done by using standard microbiological procedures. The prevalence rate of P. aeruginosa was 5.98% (n=121) among the total bacterial isolates (n=2021) and 1.02% among the total clinical specimens processed (n=11,880). Of the total 121 isolates, 84 (69.42%) were from inpatients and 37 (30.58%) from outpatient clinical samples. The prevalence of MDR and ESBL-producing P. aeruginosa was 53.71% (n=65) and 20.60% (n=25), respectively. Except, for carbapenems and piperacillin-tazobactam, the susceptibility of the isolates towards other commonly prescribed and tested antibiotics like piperacillin, tobramycin, ceftazidime, ciprofloxacin and ofloxacin were around 50.00%. The presence of MDR and ESBL producing P. aeruginosa and their resistance against most of the commonly used antibiotics in our set-up necessitates urgent and coordinated efforts to implement effective antimicrobial stewardship, strengthen infection control practices and enhance surveillance system. Addressing these issues are essential to preserve the efficacy of existing antibiotics and safeguard public health.